Urban development of the city of Bucaramanga in its projection to Smart City - Prieto - Cuentas, Narcy Carolina; Therán - Barajas, Carmen Elisa (Universidad Francisco de Paula Santander, 2022)
This ongoing research seeks to identify the basic principles on which urban development is based on its projection to Smart city, based on a review of literature and development plans, for the establishment of the aspects that contribute to a model. of smart territory in Bucaramanga, from the bibliometric analysis and the vision of the public sector against the fulfillment of development plans, taking into account, the economic, the social and the sustainable, so that the transformation of Bucaramanga in Smart City is reached from the real panorama of competitiveness of the municipality.